Comparison of Radiography and Computed Tomography for Determining Tracheal Diameter and Length in Dogs. Issue 1 (7th June 2014) - Montgomery, James E.; Mathews, Kyle G.; Marcellin‐Little, Denis J.; Hendrick, Steve; Brown, James C.
<x xml:space="preserve">Abstract</x> Objective To compare radiographic and computed tomography (CT) measurements of tracheal size as would be made for the purpose of tracheal stent size selection. Study Design Cross‐over. Animals Dogs (n = 15). Methods Canine cadavers without evidence of tracheal or respiratory disease were used for CT and digital radiography of the neck and thorax. Three observers each made 3 independent measurements at each of 5 tracheal locations, and also measured tracheal length, on each radiograph and for each CT scan on each cadaver. Results CT tracheal measurements were on average 1.03 mm larger (P < .01) compared with radiographic measurements for all 3 observers. Conclusions Radiographic measurements of the canine trachea consistently underestimate tracheal size, and CT measurements are preferable for selecting tracheal stent size.